Malaria vaccine development: State of the art and beyond - Shuyang Guo; Wenbo Sai; Min Li (​​​One Health Bulletin, 2021)
According to the statistics of the World Health Organization, malaria is still one of the main diseases affecting human health, especially in Africa, and inflicts a heavy disease burden and a huge economic burden in endemic countries. At present, the widespread emergence of antimalarial drug resistance and unresolved drug availability issues have led researchers to turn their attention to the development of antimalarial vaccines. This review aims at highlighting the recent development of malaria vaccines and discussing the challenges.